Relationship Between Feeding Practice and Stunting Incidents in Toddlers - Juwita, Helmi; Qasim, Muhammad; Sinay, Veidora Ebygeil (Omni Nursing Journal, 2025)
Background: Stunting is a condition of failure to grow due to a lack of calories and quality nutrition which results in serious long-term impacts on a child's physical growth and cognitive development. Stunting has become a global concern as one of the most critical problems in public health. Objective: This study aimed to determine the relationship between feeding practice and stunting in toddlers in Bontomanai Village, Gowa Regency. Methods: This study used quantitative research design with cross-sectional design. The sampling technique used purposive sampling with a total of 35 respondents. The study was conducted in Bontomanai Village, Gowa Regency in July-August 2024. The instruments used included Child Feeding Questionnaire (CFQ) and stunting observation sheets using direct measurements of height utilizing a microtoise. Results: There were 10 people with proper feeding practice that was 5 people (14.3%) with normal nutritional status and 5 people (14.3%) experiencing stunting. While 25 people with improper feeding practices, there were 5 people (14.3%) with normal nutritional status and 20 people (57.1%) experiencing stunting. The results of the analysis using the fisher's statistical test obtained a value of ρ=0.076 > (α=0.05), which indicated no significant relationship between feeding practice and the incidence of stunting in toddlers. Conclusion: There is no correlation between feeding practice and the incidence of stunting in toddlers in Bontomanai village, Gowa Regency. Future study needs to include larger sample size and paying attention to feeding patterns, types of food and frequency of eating in toddlers. In addition, it is also necessary to examine other factors that influence stunting.